Model Kepemimpinan Berkarakter dalam Konteks Manajemen Hubungan Masyarakat di Lembaga Pendidikan - Astuti Istikaroh (Jurnal Kependidikan, 2019)
Character leadership in educational institutions is instrumental values to move the enthusiasm of others to be willing and have a responsibility to achieve the vision of educational institutions. Characteristic leadership values that need to be inspired by leaders of educational institutions are honest, visionary, capable of being trendsetter and smart. This value becomes a terminal value or becomes an instrument value in realizing the excellence and image of educational institutions. In the context of public relations management in educational institutions, the role of character leaders is to be the main inspiration in delivering information about educational institutions to stakeholders. The importance of the role of character leaders in planning and implementing it so as to produce useful information for stakeholders.